2021
DOI: 10.1136/oemed-2021-107819
|View full text |Cite
|
Sign up to set email alerts
|

Work functioning among young adults: the role of mental health problems from childhood to young adulthood

Abstract: ObjectivesMental health problems (MHPs) during childhood and adolescence are negatively associated with having a paid job in young adulthood. Yet, little is known about how young adults function at work, that is, do they experience difficulties in meeting their job demands given their health state. This longitudinal study aims to examine the impact of MHPs from childhood to young adulthood on young adults’ work functioning (WF).MethodsData were used from 1004 participants in the TRacking Adolescents’ Individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…With respect to our effect modification results, there are relatively few studies for direct comparison to ours. A Dutch cohort assessed the association between trajectories of mental health problems and work functioning among young workers, finding that those with persistent high levels of mental health problems had lower work functioning scores, and, in particular, had difficulties in meeting their work demands 18 . Though answering a different research question, this study's finding is consistent with our finding that a history of adolescent depression modifies the association of job demands and distress.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…With respect to our effect modification results, there are relatively few studies for direct comparison to ours. A Dutch cohort assessed the association between trajectories of mental health problems and work functioning among young workers, finding that those with persistent high levels of mental health problems had lower work functioning scores, and, in particular, had difficulties in meeting their work demands 18 . Though answering a different research question, this study's finding is consistent with our finding that a history of adolescent depression modifies the association of job demands and distress.…”
Section: Discussionsupporting
confidence: 85%
“…The limitations of this study are offset by various strengths, including the population‐representative sample, the high retention of study participants over three‐time points and a 12‐year time span, and the focus on adolescence and emergent adulthood as a critical period in the natural history of mental illness and socialization 1 . Further, this study contributes to an emerging literature examining the impacts of adolescent mental health problems on the experience of work in adulthood 17,18,47 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This knowledge on phase-specific work strategies may be used to better inform and tailor supportive interventions and work accommodation to help workers to maintain working. De Groot et al (16) recently provided first insights about how young adults with a history of mental health problems function at work. It was shown that young adults with both persistent high and elevated levels of mental health problems during childhood and adolescence, compared with those with low-level mental health problems, experience difficulties in meeting their work demands for more than one day a week given a full-time work week at age 29.…”
Section: Challenges and Avenues To Support People With Common Mental ...mentioning
confidence: 99%
“…As most research so far measured common mental health problems during working adults' life, and not across the life course, knowledge on the impact of early life mental health experiences on at-work participation in later life is almost absent. Again, the findings of de Groot et al (16) highlight the importance of adopting a life course perspective by considering the concept of 'accumulation of health risk or health advantages' when connecting early life mental health experiences with work functioning. A life course perspective may also help advance future studies on the dynamics between different life domains (7), eg, the interplay between work and private life, as it recognizes an individual's life course as a multi-level developmental process shaped by the social context.…”
Section: Challenge 2: Examination Of the Complex Interdependent Relat...mentioning
confidence: 99%